Paleomagnetism of Miocene Magmatic Formations in South Kamchatka - Latyshev A.V.; Bergal-Kuvikas O.V.; Anosova M.B.; Latanova E.A. (My University, 2025)
Reconstructing the tectonic evolution of Kamchatka is crucial for deciphering the mechanisms of fold belt formation and development of subduction systems. This requires reliable paleomagnetic information for the poorly studied segments of the Koryak–Kamchatka fold region such as southern Kamchatka. This paper presents the first paleomagnetic data on Miocene magmatic bodies of the Pribrezhny complex, which is widespread on the Pacific coast of southern Kamchatka. The paleomagnetic pole calculated for the Miocene of southern Kamchatka from 33 sites is statistically significantly different from all the published Cenozoic poles in the nearby regions. The new data indicate the formation of Miocene volcanics at a paleolatitude close to the present position (52.3°) and support the formation of the Miocene supra-subduction volcanic belt on the more ancient basement of the Olyutor–Kamchatka fold system rather than within a separate exotic block. It is shown that most of the sampled volcanics formed before the main phase of tectonic deformation, but at least part of the studied normal-polarity bodies contain postfolding magnetization and may represent products of younger episodes of magmatism.
Keywords: 38.21.03 Методы геологической съемки; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene